Language Politeness in The Novel "Ketika Cahaya Rembulan Mengecup Lautan" By Anisha Dayu on Wattpad Application - Ekasari, Denis; Mardikantoro, Hari Bakti; Haryadi, Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Language has an important role in communication and interaction between humans in everyday life. Speak politely to create effective communication. This study aims to describe the politeness of language in the novel "Ketika Cahaya Rembulan Mengecup Lautan" by Anisha Dayu on the wattpad application. This study examines the observance of language politeness. Politeness theory in this study uses ten politeness thimbles based on Leech's theory of politeness. This research approach uses a theoretical approach and a qualitative descriptive methodological approach. The data of this research are fragments of speech in the novel. The method used in this study is the equivalent and normative methods. with basic listening techniques and advanced techniques, namely note-taking techniques. The results of the study, language is an important role in everyday life. There is politeness in it. In this study, nine politeness thimbles were found which allegedly adhered to the principles of politeness in language. Research related to language politeness has been carried out by several researchers, one of which is Cahyani's research in 2019. This research examines language politeness compliance, language politeness violations and factors that influence the occurrence of language politeness in students' speech acts in interacting at Tidar University. The benefits of this research are in linguistic learning, especially pragmatics related to language, then for teachers and the public and other researchers. For universities, this research can be a source of learning for Indonesian language learning in the school environment.